2021
DOI: 10.3389/fbioe.2021.765596
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Menisci on Tibiofemoral Contact Mechanics in Human Knees: A Systematic Review

Abstract: Purpose: Menisci transfer axial loads, while increasing the load-bearing tibiofemoral contact area and decreasing tibiofemoral contact pressure (CP). Numerous clinical and experimental studies agree that an increased CP is one predominant indicator for post-traumatic osteoarthritis (PTOA) of the knee joint. However, due to the immense variability in experimental test setups and wide range of treatment possibilities in meniscus surgery, it is difficult to objectively assess their impact on the CP determination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 86 publications
1
21
0
1
Order By: Relevance
“…Of these, even though the presence of an 83% width tear of the posterior horn during the preswing resulted in the most significant increase in cartilage load, the cartilage/total load ratio increased by only 9%. The findings suggested that medial meniscus radial tears have lesser influence on the tibial cartilage loading ( Figure 5 ), consistent with previous experimental results ( Bedi et al, 2010 ; Bedi et al, 2012 ), however, some studies have also concluded that meniscal tears lead to increased cartilage loading ( Zhang et al, 2015 ; Sukopp et al, 2021 ). Previously, investigators have pointed out that meniscal tears in a healthy knee may ultimately lead to the occurrence of knee OA due to the loss of much of the meniscal functionality, such as circumferential stress transmission ( Englund et al, 2009 ).…”
Section: Discussionsupporting
confidence: 90%
“…Of these, even though the presence of an 83% width tear of the posterior horn during the preswing resulted in the most significant increase in cartilage load, the cartilage/total load ratio increased by only 9%. The findings suggested that medial meniscus radial tears have lesser influence on the tibial cartilage loading ( Figure 5 ), consistent with previous experimental results ( Bedi et al, 2010 ; Bedi et al, 2012 ), however, some studies have also concluded that meniscal tears lead to increased cartilage loading ( Zhang et al, 2015 ; Sukopp et al, 2021 ). Previously, investigators have pointed out that meniscal tears in a healthy knee may ultimately lead to the occurrence of knee OA due to the loss of much of the meniscal functionality, such as circumferential stress transmission ( Englund et al, 2009 ).…”
Section: Discussionsupporting
confidence: 90%
“…У разі конгруентних суглобових поверхонь суглобовий хрящ розцінюється як незначний амортизатор, так як товщина суглобового хряща становить 1-4 мм. З цієї точки зору важливішими є меніски, які заповнюють суглобову щілину у різні фази руху [15]. Однак функція гіалінового хряща й менісків, як і зв'язок з сухожилко-м'язовим апаратом, є недостатньою при наявності або виникненні внутрішньосуглобової деформації кістки [16].…”
Section: результати та їх обговоренняunclassified
“…A recent review on the impact of different test setups and meniscal states on the tibiofemoral contact pressure indicated a major impact of the applied axial load on the CPpeak [47]. The CPpeak measurements of the present study were in the same range of those reported in the intact state and after performing a total LMM under an applied axial loading of 200 N. In their MAT study, Paletta et al [35] applied 1,800 N axial loading and showed a CPpeak increase of up to 335% after LMM compared to the intact meniscus state.…”
Section: Lateral Tibiofemoral Contact Mechanicsmentioning
confidence: 99%